(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to: 1-Building a training program based on high-impact strategies (HITS) for teachers of the Arabic language in the preparatory stage. 2-Knowing the effectiveness of the strategy-based training program based on high-impact strategies (HITS) in developing the teaching competencies of Arabic language teachers in the preparatory stage. To achieve the research goals; The researcher followed the procedures of the descriptive approach, and the procedures of the experimental approach, as the researcher prepared a training program consisting of (10) training units with (30) sessions, and the researcher verified its validity by presenting it to a group of arbitrators, and in order to identify the effectiveness of the training program in developing teaching competencies ; The researcher relied on an experimental design with partial control, which is the one-group, non-randomized choice design with two tests (pre and post). General Education Department in Diyala Governorate / Khalis Education Department. As for the research tool, the researcher prepared a (note card) for teaching competencies, after examining the literature, sources, and previous studies related to the subject of her research. A sub-field, and (51) paragraphs, and to achieve the apparent validity of the research tool, it was presented to a group of arbitrators and specialists to find out their opinions and judgment on the validity of the fields and paragraphs, so that the note card becomes its final form after modifying and deleting some paragraphs (44) paragraphs, as well as establishing the construction validity of the paragraphs The observation card, after applying it to an exploratory sample of (30) male and female teachers, and after verifying the validity of the tool, the researcher extracted the reliability coefficient, which amounted to (0.79) , and it is considered a good stability coefficient. The research sample. The researcher trained the research sample according to the training program based on high-impact strategies (HITS), and then re-applied the observation card (dimensionally) on the research sample. To find out the size of the impact and effectiveness of the training program and the rate of development in the teaching competencies of Arabic language teachers in the preparatory stage (the research sample), and in the light of this result, I concluded that the training program contributed to the development of the teaching competencies of Arabic language teachers in the preparatory stage by (26%), and in In light of the research results, the researcher made several recommendations, including: Adopting a training program based on High Impact Strategies (HITS) in in-service training programs for Arabic language teachers, because of its positive impact on their teaching competencies, and as a complement to the current research, the researcher suggested several proposals, including: - Examining the effectiveness of a training program based on high-impact strategies (HITS) for (applicants) students in improving professional readiness